Comparative Study Of Murabaha Financing At Kalbar Syariah Bank And Mandiri Syariah Bank Branch Sambas - Vera Ayu Oktovia Sari; Sri Deti; Ubabuddin (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2023)
One of the most popular Fiqh schemes used by Islamic banking is the Murabaha Buy-Sell Scheme. This Murabahah transaction was commonly carried out by the Prophet Muhammad, and his companions. The activities of Islamic banks are to collect funds from customers, distribute funds and other banking services. Islamic banks in its operations started from the collection of public funds in the form of demand deposits, savings and deposits. The funds raised were distributed in the form of financing, namely Murabaha, Musharakah, qardh, ijarah and services financing. The funds were distributed to customers in the form of working capital financing, consumption financing, working capital financing and investment. The focus of this study are: 1) How is the practice of Murabaha financing in Kalbar Syariah Bank Sambas branch? 2) What is the practice of Murabaha financing at Syariah Mandiri Bank Sambas branch? 3) What is the comparison of Murabaha financing at Kalbar Syariah Bank and Syariah Mandiri Bank Sambas branch? The purpose of this study was to describe, identify, uncover and analyze the financing practices in Kalbar Syariah Bank and Syariah Mandiri Bank branch sambas. This research is a field research (Field research) or qualitative research, qualitative research is more emphasis on the process than the product or outcome. Qualitative research focuses more on research that is a process, such as interaction between humans in a community, the process of implementing work, the development of a symptom or civilization. The researcher concluded that in distributing Murabaha Financing Kalbar Syariah Bank and Syariah Mandiri Bank both provide the conditions set by Bank Indonesia, and in the Murabaha financing process there is a difference between the total amount of financing installments of the two banks. Syariah Mandiri Bank Murabaha financing cheaper than Kalbar Syariah Bank, but judging from the interest of customers who do the financing, between Syariah Mandiri Bank with Kalbar Syariah Bank is more interested in financing at Kalbar Syariah Bank. The reason why the interest in Kalbar Syariah Bank is more than in Syariah Mandiri Bank, because the financing process, especially on the terms and the decision process does not take a long time and quickly.